Memoria E Progetto = MEMORY AND PROJECT - Pellerey, Michele (Rivista di scienze dell'educazione, 2021)
The relationship between memory and project can be considered from many points of view. The contributtion aims at exploring some of them from an educational perspective. From a subjective and personal point of view, the role of experience and the establishment of consolidated habits is immediately highlighted; while the attitudes developed in relation to these experiences influence the present and future projects. In this context attention is drawn to the self-determination and self-regulation processes involved. At the collective and social level, the processes associated with enterprise and entrepreneurship and the role of awareness of one's own cultural heritage emerge. Today the expression "memory" also refers to the technological world and big data, to the use that can be made of it for better or worse. The algorithms designed to exploit these databases are the projects of the computing world. (English)